2013
DOI: 10.1128/jb.01881-12
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis Response Regulator Gene degU Is Positively Regulated by CcpA and by Catabolite-Repressed Synthesis of ClpC

Abstract: In Bacillus subtilis, the response regulator DegU and its cognate kinase, DegS, constitute a two-component system that regulates many cellular processes, including exoprotease production and genetic competence. Phosphorylated DegU (DegU-P) activates its own promoter and is degraded by the ClpCP protease. We observed induction of degU by glucose in sporulation medium. This was abolished in two mutants: the ccpA (catabolite control protein A) and clpC disruptants. Transcription of the promoter of the operon cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
0
23
1
Order By: Relevance
“…We then tried to determine whether Hpr or Hpr-Ser 45 -P could further stimulate CcpA Bt binding to cre chiB . Hpr and HprSer 45 -P (2 M each) were mixed in the mixture for the reaction of CcpA Bt with Pcre. We found that Hpr did not increase the affinity of CcpA Bt for the DNA fragments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then tried to determine whether Hpr or Hpr-Ser 45 -P could further stimulate CcpA Bt binding to cre chiB . Hpr and HprSer 45 -P (2 M each) were mixed in the mixture for the reaction of CcpA Bt with Pcre. We found that Hpr did not increase the affinity of CcpA Bt for the DNA fragments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, secondary control mechanisms may finetune expression in response to external and internal conditions or signals through DegU, ComA, and ScoC. For example, DegU is induced by the presence of glucose through catabolite regulator function (63). Thus, a DegU-dependent timing mechanism may exist for initial repression by dephospho-DegU, followed by activation through DegU phosphorylation and inhibition of motility (64).…”
Section: Discussionmentioning
confidence: 99%
“…The P2 promoter, which is located upstream of the degU P3 promoter, has been known to be activated only by the transcription factor TnrA either under nitrogen starvation conditions or in a disruptant of glnA encoding glutamine synthetase (2,43). The putative TnrA-binding site, the region from nucleotides Ϫ145 to Ϫ129 relative to the transcription start site of P3, is overlapped by the catabolite control protein A (CcpA)-binding sequence (44). In the presence of glucose, the degU P3 promoter is positively controlled by CcpA.…”
Section: Discussionmentioning
confidence: 99%